Forsythia suspensa leaf fermented tea extracts attenuated oxidative stress in mice via the Ref-1/HIF-1α signal pathway and modulation of gut microbiota - Li, Lijuan; zhao, Yating; Ding, Yuxin; Guo, Lanze; Dai, Ruiyao; Chen, Aixiang; Duan, Guofeng (Scientific reports, 2025)
Forsythia suspensa leaf fermented tea (FSLFT) is made from tender buds of Forsythia suspensa collected in spring. The main active components of FSLFT include forsythiaside, forsythia ester glycoside, rutin, and forsythia flavonoids, which have antibacterial, antioxidant, liver-protective, and immune-regulatory effects. Oxidative stress can trigger excessive apoptosis in intestinal epithelial cells, leading to dysfunction of the small intestinal mucosa and impaired intestinal absorption. This study focused on Kunming mice as research subjects and used hydrogen peroxide as an inducer to investigate the antioxidant and anti-inflammatory effects of FSLFT in vivo, as well as its regulatory effects on the intestinal microbiota of mice. The aim of this study was to establish a theoretical foundation for the functional study of Forsythia suspensa leaves and provide specific recommendations for their growth and application. The results showed that H 2 O 2 treatment led to an increase in oxidative levels in mice. FSLFT has been shown to have antioxidant effects via the Redox Factor-1(Ref-1)/ hypoxia-inducible factor-1 alpha (HIF-1α) pathway, reduce inflammation caused by hydrogen peroxide through the Toll-like receptor 4 (TLR4)/nuclear factor kappa-B (NF-κB) signaling pathway, and protect mouse colons from oxidative stress by repairing gut microbiota imbalance and increasing microbial diversity and abundance. These findings establish a theoretical basis for studying the functional properties of FSLFT.